A highly efficient atomic nickel catalyst for CO2 electroreduction in acidic electrolyte. Issue 34 (11th April 2023) - Wu, Qiao; Liang, Jun; Han, Li-Li; Huang, Yuan-Biao; Cao, Rong
Abstract : A highly efficient atomic nickel catalyst Ni-SAC-800 with high porosity and conductivity has been developed to show excellent performance for CO2 electroreduction in acidic conditions. Abstract : The development of single atom catalysts (SACs) for CO2 electroreduction in acidic electrolytes can greatly improve the CO2 utilization efficiency but remains challenging. We report a carbon-embedded atomic nickel catalyst prepared from carbon black, porphyrin and nickel(ii ) salts. The catalyst shows excellent activity for CO2 reduction with high CO faradaic efficiency of 99.9% and an industrial-level CO partial current density of 296.4 mA cm −2 in acidic media, which indicates the importance of carbon-supported SACs.